Back-End Dynamic Generation Of Media Object Presentations In E-Learning Using XSLT - Khor, Ean Teng (2007)
The thesis decribes the work of research to perform dynamic method in back-end generation of media object presentations in e-Learning. The thesis discusses the implementation of dynamic techniques to generate media presentations in Learning Management System(LMS) using XML/XSLT-based Technologies.